2002
DOI: 10.1097/00005110-200212000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Staffing on Patient Outcomes Across Specialty Units

Abstract: Results from this study suggest that the impact of staffing on outcomes is highly variable across specialty units; however, when present, the relationships are inversely related with lower staffing levels, resulting in higher rates of all outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 10 publications
2
65
0
7
Order By: Relevance
“…2,7,[11][12][13][14][15] The findings of this study show that continued research in this area is needed to explore possible relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,7,[11][12][13][14][15] The findings of this study show that continued research in this area is needed to explore possible relationships.…”
Section: Discussionmentioning
confidence: 99%
“…11 Yet, despite these known potential complications, physical restraint use in critical care environments continues both internationally and in the United States. 2,[11][12][13] Published reports show that it is the nurses who decide whether or not to restrain a patient with a physician's verbal order often obtained after physical restraints have been applied, if at all. 14 In looking at various factors that can influence this decision, no consensus is apparent in the research findings to support a relationship between staffing, experience level, education level, nurses' attitudes toward use of physical restraints, and practice issues related to use of physical restraints (ie, nurses' actions while caring for patients who are restrained).…”
mentioning
confidence: 99%
“…Nurse demand methods for staffing and nursing workload (which may not be incorporated in the staffing methodology) have come under particular scrutiny (12). Patient/nurse ratios, although a relatively crude measure, are easily determined and have been linked to several adverse patient occurrences in the ICU, including nosocomial infections, falls, medication errors, and postoperative respiratory and cardiac complications (13)(14)(15). Associations between nurse staffing and UE have been less evident (16 -18), although one recent pediatric study concluded that an UE was more likely to occur when a nurse was assigned two patients rather than one (19).…”
mentioning
confidence: 99%
“…21,22 The results of several studies support these ideas: more frequent interruptions are associated with more errors, 23 and having more nurses on staff is associated with fewer errors. 24 Use of signage and checklists may minimize distractions during critical phases of administration and may reduce errors overall. 25 For higher risk medications, having a second nurse or pharmacist provide a double check on the medication may also be beneficial.…”
Section: Nursing Interventionsmentioning
confidence: 99%